EFFECTS OF POINT-LOSS PUNISHERS ON HUMAN SIGNAL-DETECTION PERFORMANCE - Lie, Celia (Society for the Experimental Analysis of Behavior, Inc, 2009)
Three experiments using human participants varied the distribution of point-gain reinforcers or point-loss punishers in two-alternative signal-detection procedures. Experiment 1 varied the distribution of point-gain reinforcers for correct responses (Group A) and point-loss punishers for errors (Group B) across conditions. Response bias varied systematically as a function of the relative reinforcer or punisher frequencies. Experiment 2 arranged two conditions – one where an unequal ratio of reinforcement (5∶1 or 1∶5) was presented without punishment (R-only), and another where the same reinforcer ratio was presented with an equal distribution of point-loss punishers (R+P). Response bias was significantly greater in the R-only condition than the R+P condition, supporting a subtractive model of punishment. Experiment 3 varied the distribution of point-gain reinforcers for correct responses across four unequal reinforcer ratios (5∶1, 2∶1, 1∶2, 1∶5) both without (R-only) and with (R+P) an equal distribution of point-loss punishers for errors. Response bias varied systematically with changes in relative reinforcer frequency for both R-only and R+P conditions, with 5 out of 8 participants showing increases in sensitivity estimates from R-only to R+P conditions. Overall, the results indicated that punishers have similar but opposite effects to reinforcers in detection procedures and that combined reinforcer and punisher effects might be better modeled by a subtractive punishment model than an additive punishment model, consistent with research using concurrent-schedule choice procedures.